Influence of the oclusal plane on mandibular adaptation in hyperdivergent skeletal Class II malocclusions - Ramos Zavala, César Ignacio (2023)
Hyperdivergent Skeletal Class II malocclusion is one of the most difficult to treat due to the different components involved in this type of malocclusion, whether due to maxillary or mandibular involvement or both. The objective of this review is to update the knowledge on how the occlusal plane influences the anticlockwise rotation of the mandible, which is a key point in the successful treatment of hyperdivergent skeletal Class II malocclusion due to mandibular retrusion. Two different approaches are also presented in the management of the occlusal plane and therefore of the vertical dimension in this type of patient; the first emphasizes molar intrusion as a vertical control measure to avoid a mandibular clockwise rotation and the other bases the treatment on molar extrusion increasing the postero-superior vertical dimension which could bring the mandible to a more advanced, physiological and functional position, bringing I get a condylar adaptation. In this sense, the management of the occlusal plane can be achieved in adolescent patients without growth by means of the multiloop edgewise arch wire (MEAW) and in growing patients by means of the extraoral arch (AEO). It can be concluded that both treatment schemes can be valid; However, more clinical studies are needed to demonstrate that which represents long-term treatment stability while maintaining adequate mandibular function and adaptation and which has an impact on an aesthetic improvement of the facial profile.